Developmental Exposure to Endocrine Disrupting Chemicals and Type 1 Diabetes Mellitus - Howard, Sarah G. (Frontiers in Endocrinology, 2018)
Exposure to endocrine disrupting chemicals (EDCs) may have implications for the development of type 1 diabetes mellitus (T1DM), especially if exposure occurs during development. Exposure to EDCs during fetal or early life can disrupt the development of both the immune system and the pancreatic beta cells, potentially increasing susceptibility to T1DM later in life. Developmental exposure to some EDCs can cause immune system dysfunction, increasing the risk of autoimmunity. In addition, developmental exposure to some EDCs can affect beta cell development and function, influencing insulin secretion. These changes may increase stress on the beta cells, and identify them as a target to the immune system. Developmental exposure to EDCs that disrupt metabolism by increasing insulin resistance or obesity may also stress the beta cells. Exposure to these EDCs during development may play a role in the pathogenesis of T1DM, and requires further research.